Legislative framework of career guidance and counselling in Serbia - Miljković Jovan; Čairović-Pavlović Neda; Robertson Kristina (Nastava i Vaspitanje)
The concept of career has undergone a significant transformation in recent decades. It has become less linear and more heterogeneous and multifaceted, often marked by frequent changes and numerous parallel and lateral paths. Within this context, career guidance and counselling (CGC) has emerged as a leading concept in various sector polities, both in the European Union and in Serbia, and is undoubtedly at the forefront of educational polities. For career guidance and counselling to be managed adequately and to optimize its expected outcomes, it is necessary to have a consistent, carefully designed legislative framework in place. Using a qualitative research approach, we conducted our research with the aim of discovering how the phenomenon of career guidance and counselling is perceived in the legislative documents of the Republic of Serbia. We decomposed the main research question into seven CGC elements to be observed: understanding of the concept, objectives, programmes, carriers of activity, career practitioners, target groups, and effects. We used a descriptive and comparative method to analyse 19 documents in the sectors of youth, education (from primary school to adult education) and employment, with the aim of covering all ages and life roles in which CGC may be relevant. The research results indicate that CGC, as a cross-sectoral activity, is unevenly articulated across different polity sectors. There is a predominant orientation towards youth, the education sector, and the service of informing about career, out of the three areas of CGC services. The study highlights the need to adopt an integrating document and to establish a body to coordinate activities of CGC as well as the obligation to apply existing CGC standards.